Low dose IR-induced IGF-1-sCLU expression: a p53-repressed expression cascade that interferes with TGFβ1 signaling to confer a pro-survival bystander effect - Klokov, Dmitry (2012)
Inadvertent mammalian tissue exposures to low doses of ionizing radiation (IR) after radiation accidents, remediation of radioactive-contaminated areas, space travel, or a dirty bomb represents an interesting trauma to an organism. Possible low dose IR-induced bystander effects could impact our evaluation of human health effects, since cells within tissue are not equally damaged after doses of IR ≤10 cGy. To understand tissue responses after low IR doses, we generated a reporter system using the human clusterin promoter fused to firefly luciferase (hCLUp-Luc). Secretory clusterin (sCLU), an extra-cellular molecular chaperone, induced by low doses of cytotoxic agents, clears cell debris. Low dose IR (≥2 cGy) exposure induced hCLUp-Luc activity with peak levels at 96 h, consistent with endogenous sCLU levels. As doses increased (≥1 Gy), sCLU induction amplitudes increased and time to peak response decreased. sCLU expression was stimulated by IGF-1, but suppressed by p53. Responses in transgenic hCLUp-Luc reporter mice after low IR doses showed that specific tissues (i.e., colon, spleen, mammary, thymus, bone marrow) of female mice induced hCLUp-Luc activity more than male mice after whole body (≥10 cGy) irradiation. Tissue-specific, non-linear dose- and time-responses of hCLUp-Luc and endogenous sCLU levels were noted. Colon maintained homeostatic balance after 10 cGy. Bone marrow responded with delayed, but prolonged and elevated expression. Intraperitoneal administration of α-TGFβ1 (1D11), but not control (13C4) antibodies, immediately following IR exposure abrogated CLU induction responses. Induction in vivo also correlated with Smad signaling via activated TGFβ1 after IR. Mechanistically, media with elevated sCLU levels suppressed signaling, blocked apoptosis and increased survival of TGFβ1-exposed tumor or normal cells. Thus, sCLU is a pro-survival bystander factor that abrogates TGFβ1 signaling and promotes wound healing.